2013
DOI: 10.1186/1475-2840-12-115
|View full text |Cite
|
Sign up to set email alerts
|

Impaired skin microcirculation in paediatric patients with type 1 diabetes mellitus

Abstract: Aims/hypothesisWe used Laser Doppler Fluximetry (LDF) to define "normal" endothelial function in a large cohort of healthy children and adolescents and to evaluate skin microcirculation in paediatric patients with type 1 diabetes mellitus.MethodsLDF was performed in 102 healthy children (12.8 ± 3.3 years of age; 48 male) and 68 patients (12.9 ± 3.3 years of age; 33 male). Duration of disease was 5.0 ± 3.97 years. Each participant sequentially underwent three stimulation protocols (localized thermal hyperaemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 30 publications
1
32
0
2
Order By: Relevance
“…Heat challenge to the skin is usually applied using a thermostatic heating probe device made of solid metal (13,41,47). But this method is not practical in the case of the gingiva because its surface is curved; in addition, the heating device could mechanically compress the thin gingival tissues including vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Heat challenge to the skin is usually applied using a thermostatic heating probe device made of solid metal (13,41,47). But this method is not practical in the case of the gingiva because its surface is curved; in addition, the heating device could mechanically compress the thin gingival tissues including vessels.…”
Section: Discussionmentioning
confidence: 99%
“…As control group for microvascular function we used data from 82 healthy children, which was obtained previously for another study by our workgroup [18]. Furthermore, normal plasma levels for Ang 1 and Ang 2 were obtained from a group of 38 age-matched healthy children for this study.…”
Section: Data Sources and Measurementsmentioning
confidence: 99%
“…Optical assessment of skin microvascular function has been used for diagnostic purposes in adults for more than 20 years [13][14][15][16], and in recent years cutaneous laserDoppler fluximetry (LDF) has become accepted as an easy and noninvasive method to investigate microcirculation and/or the neurogenic vasodilation response secondary to physical or pharmacological stimulation in children [17,18]. A study of both cross-sectional and longitudinal design in adults with end-stage renal disease revealed that an impaired cutaneous local thermal hyperemic response was associated with increased cardiovascular mortality [5].…”
Section: Introductionmentioning
confidence: 99%
“…Нарушения функций эндотелия приводят к нарушению синтеза NO, что отражается в снижении постокклюзи-онной реактивной гиперемии, по степени выраженно-сти которой исследователи судят об объемах резервов кровотока [21,22]. Для оценки эндотелиальной функ-ции у пациентов с СД могут применяться и другие виды функциональных воздействий: фармакологические и температурные пробы [50]. Дисфункция эндотелия в этих случаях также проявляется снижением вазодила-таторной реакции на стимулы.…”
Section: применение лдф для оценки микроциркуляции у пациентов с сдunclassified
“…Было показано, что в формировании температурной вазоди-латации участвуют как эндотелий, так и аксональные рефлексы [23]. Оценка с помощью одного вида воздей-ствия сразу нескольких звеньев регуляции микроцирку-ляторной сети, на каждом из которых могут наблюдаться изменения, приводит к увеличению вероятности обнару-жения статистически значимых отклонений микроцир-куляции у пациентов с СД [50,51].…”
Section: применение лдф для оценки микроциркуляции у пациентов с сдunclassified